Raoiella indica (Prostigmata: Tenuipalpidae): The Red Palm Mite: A Potential Invasive Pest of Palms and Bananas and Other Tropical Crops of Florida - Jorge E. Peña; Catharine M. Mannion; Forrest W. Howard; Marjorie A. Hoy (EDIS)
ENY-837, an 8-page illustrated fact sheet by J. E. Peña, C. M. Mannion, F. W. Howard and M. A. Hoy, describes this important pest of coconut fruit in many tropical countries, with recent findings in the Caribbean. Damage, description of stages, life cycle, seasonality, dispersal, host plants, chemical control, natural enemies, pathogens, and detection are discussed. Includes references and table of host plants. Published by the UF Department of Entomology and Nematology, November 2006.